PERBEDAAN WAKTU PUASA DI WILAYAH ABNORMAL DAN APLIKASI HUKUMNYA - Sunarto Sunarto (Kordinat: Jurnal Komunikasi antar Perguruan Tinggi Agama Islam, 2018)
Etymologically fasting is "al-imsak" (restraint). As for the terminology, fasting is: "To refrain from something that can cancel the fasting starting from the dawn until the sun sets with aim." This is the definition of Fuqaha "in understanding the time limit of fasting according to QS. al-Baqarah: 187. In reality, when we apply the definition of fasting, there is a significant difference between one region and another. For example, the area around the equator, relatively stability between daytime and night. However, there is a contrast difference to the regions around the pole (north-south). If the area far from the equator the more contrast the time difference occurs. This means that the farther the area from the equator, the longer the time of daytime or night. Besides the influence of the above factors, there is also the current position of the sun. It determines whether the sun is in the north or the south of the earth? The implication that when the fast of Ramadan coincides with the summer, from March to September is in the north. The climax of June 21, the sun has a maximum declination (d = 23 '30'), then the regions in the north have experience a longer noon inversely proportional to the regions in the south. If the regions are closer to the pole, the more extreme the daytime and night difference occurs, that is called the area/circumpolar region. To apply the fasting law (circumpolar) fasting area, by following the International Fatwah Majlis, that is in two ways: first, following the fasting period of the Hijaz (Makkah-Madinah), second, following the nearest region/country that has a daytime or night limit.